Case report: Self-performed orthopedic exams in telehealth treatment of a youth athlete with acute rotator cuff strain - Wang, Yuxuan; Yi, Nuo; Ericksen, Hayley M.; Zhang, Wupeng (Frontiers in Sports and Active Living, 2023)
Background Sports-related rotator cuff muscle injury is one of the most prevalent pathologies affecting overhead sports athletes. Since the COVID-19 pandemic and its subsequent stay-at-home protocols, physical therapy has transited into a new realm of telehealth. Current evidence regarding examining and managing RTC strain in telehealth physical therapy is minimal. Case presentation A self-referred 14-year-old female Chinese semi-professional tennis player presented with an acute right RTC strain. The mechanism of injury involved forehand strokes with left trunk rotation. No ligamentous or labral damage was observed on Magnetic Resonance Imagining. The individualized care plan included virtual partner-assisted assessment, online instructions on therapeutic exercises, and education with psychosocial considerations. Outcome and follow-up After a 6-week intervention, the patient demonstrated complete shoulder range of motion, full muscle strength, complete return-to-practice, 0% Quick DASH disability index, and 6/68 on the Tampa Scale for kinesiophobia. Discussion This case report demonstrated that telehealth is an accessible and cost-effective option for youth tennis athletes with RTC strain. This unique case showed a detailed roadmap from examination to discharge of this plan of care. There are also barriers including test and measure validity, and communication difficulties to be considered. Despite the challenges, this case was a good example of telehealth being an effective, repeatable, and cost-efficient option for patients with poor healthcare access.